Development of material selection method for the application children bicycle frame - Maleque, Md. Abdul; Sarker, Dyuti (2010)
A bicycle frame is a crucial part for cycling performance, efficiency, comfort, and injury prevention. This is especially true in the case of children cyclists that do not have the necessary cycling experience, balance and the fully developed musculoskeletal system of the adults. The selection of the correct materials for a particular product especially a children bicycle frame is a key step in the design and development process because it will carry the load of the rider during cycling. In the present paper few methods have been developed to select material of a bicycle frame for children and teenagers 7–14 years old. This paper will present the development of the material selection methodology based on Ashby’s material selection chart for the application of bicycle frame purposes. Two quantitative methods are proposed such as cost per unit strength and digital logic model methods. Also mechanical properties, including tensile strength, yield strength, Young’s modulus, toughness, density as well as cost were used as the key parameters in the material selection stage. Among the material selection methods the development of digital logic model is the best suited method which identified that the Kevlar fiber reinforced plastics (KFRP) as the most appropriate candidate material for the application of children bicycle frame.